Plantas transgênicas de tabaco expressando RNA hairpin e jaburetox como estratégias para controle de Helicoverpa armigera - Ceccon, Cássia Canzi (2019)
Helicoverpa armigera is a serious insect-pest in several regions of the world and there are reports of populations resistant to various groups of currently used insecticides and Bt toxins. Considering these factors, the need to search for new H. armigera control strategies is clear. Technologies such as oral delivery of RNA interference (RNAi) inducing molecules that induce mortality by silencing vital target pest genes and the use of new insecticidal biomolecules, such as the Jaburetox (JBTX) recombinant insecticidal peptide, derived from one of the Canavalia ensiformes urease isoforms, are strategies that can be used to control pest insect, including H. armigera. The objective of this work was to produce genetically modified tobacco plants containing genes expressing: 1) hairpin RNA molecules (hpRNA) that form doble- strand RNA (dsRNA) complementary to the H. armigera rieske gene (hpRNA-rieske); and/or, 2) the entomotoxic Jaburetox peptide (JBTX), and evaluate their efficacy in inducing mortality in H. armigera fed on these plants. High mortality and reduced consumption were verified in larvae fed on the R12/2 event containing the gene encoding hpRNA-rieske and on J22/4 event containing the gene encoding the JBTX peptide. Feeding of the larvae with the hpRNA-rieske event resulted in a reduction in the level of the rieske gene transcripts in the digestive system and in the remaining tissues of the larvae body by 85%. Using the best events (R12/2 and J22/4) as parents, progenies of containing both genes of interest were obtained through the crosses J22/4xR12/2 and R12/2xJ22/4. These stacked plants, hemizygous for both genes, induced similar mortality in H. armigera as the R12/2 parent. This parent displays segregation of hpRNA-rieske in offspring suggesting it is homozygous; however, it could also carry more than one copy of hpRNA-rieske as a result of multiple insertions in the genome. It is hypothesized that the evaluation of J22/4 and R12/2 hybrids developed in the future to be homozygous for both genes may provide even higher control of H. armigera. In addition, further studies may indicate the occurrence of interaction between insecticidal substances and the feasibility of using both technologies together in a stacked approach.